Zuhd and the Making of the Sufi Self: Ethical and Epistemological Shifts in Early Islamic Piety - Shadiqin, Sehat Ihsan; Wahyudi, M. Agus; M. Ikhwan; Hidayati, Tuti (KALAM, 2025)
This article examines the historical transformation of zuhd (asceticism) into Sufism as a significant ethical and epistemological development in early Islamic spirituality. While previous studies have explored the origins of Sufism, relatively little attention has been given to how this transition reshaped the moral and intellectual formation of the religious subject. This study therefore investigates the emergence of what may be called the “Sufi self” through the gradual transformation of early Islamic ascetic practices. Using a historical–textual approach, the article analyzes the teachings of three influential figures in early Islamic piety: al-Ḥasan al-Baṣrī, Rābiʿah al-ʿAdawiyyah, and al-Ḥārith al-Muḥāsibī. Their ethical and spiritual teachings illustrate the shift from an ascetic discipline grounded in fear of divine judgment toward a more interiorized spirituality centered on love, introspection, and self-knowledge. By situating these developments within the socio-historical context of early Abbasid society, the study shows how changing social conditions contributed to the interiorization of religious practice. The findings suggest that the emergence of the Sufi self represents not a rupture with early Islamic asceticism but its transformation into a reflective spiritual anthropology in which ethical vigilance becomes a form of epistemic self-awareness. This study contributes to the broader understanding of early Sufism by demonstrating how the ascetic ethos of zuhd evolved into a systematic discipline of inner knowledge and moral self-examination.